IMPLEMENTASI AKUNTANSI AGRIKULTUR PADA PERUSAHAAN SEKTOR PERTANIAN DI INDONESIA - Ravi Choirul Anwar; Amrie Firmansyah (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2020)
This study aims to review the implementation of agricultural accounting in Indonesia Agricultural Sector Companies. The research method used in this study is a qualitative method using content analysis. The data taken as the object of study are all the company's 2016-2018 annual financial statements which are the periods before and after the effective effect of PSAK 69 and PSAK 16 on agricultural sector companies listed on the Indonesia Stock Exchange. The objects are 14 companies. The results suggest that in the accounting treatment of biological assets and agricultural products, none of the companies implemented the early adoption of PSAK 69 (2015) and apply accounting treatment in accordance with PSAK 69 in 2018. Related to biological assets in the form of productive plants, almost all companies have applied accounting treatment in accordance with PSAK 16 (revised 2015). The effectiveness of PSAK 69 (2015) provides significant changes to the accounting treatment of biological assets owned by companies, especially related to agricultural products. The treatment has an impact by increasing the company's assets by recognizing agricultural products as biological assets that were not previously recognized and recorded by the company. Meanwhile, related to biological assets in the form of live animals and edible plants that had been previously recognized by the company, there was a change in measurement using fair value fewer costs to sell, thereby affecting fluctuations in the company's profit and loss. The entry into force of PSAK 69 (2015) also uniforms the recognition and measurement of biological assets by companies.